2015
DOI: 10.1002/lary.25221
|View full text |Cite
|
Sign up to set email alerts
|

Oral pseudoephedrine decreases the rate of transmucosal nitrous oxide exchange for the middle ear

Abstract: Objective Determine if oral pretreatment with a vasoconstrictor decreases the blood to middle-ear exchange-rate of the perfusion-limited gas, Nitrous Oxide (N2O). Study Design Randomized, double-blind, crossover study. Methods Ten adult subjects with and 10 without past middle-ear disease completed paired experimental sessions, identical but for oral pretreatment with either pseudoephedrine HCL or lactose placebo. At each session, subjects were fitted with a non-rebreathing mask and breathed room air for 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
1

Year Published

2015
2015
2017
2017

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(17 citation statements)
references
References 33 publications
1
15
1
Order By: Relevance
“…Simulations 5 and 6 predict that a downgraded ET opening efficiency will be expressed as a less efficient MEPR for those periods which is accompanied by a consequent negative shift in the EV-MEEPG, effects validated by the change in MEEPG (tympanometric pressure) observed for children and adults during natural and experimental upper respiratory viral infections (Antonio et al, 2002; Buchman et al, 1995; Moody et al, 1998). In addition, emergent features of the model such as physiologic ME species-pressures (Simulation 6), the negative EV-MEEPG for all ET opening efficiencies not equal to 1 (Simulation 3), and the perfusion-limitation on the rate of MEEPG change (Simulations 2, 3) are consistent with clinical measurement (Antonio et al, 2002; Felding et al, 1987; Hergils et al, 1990; Hergils et al, 1997; Moody et al, 1998; Sade et al, 1993) and experimental results (Buchman et al, 1995; Teixeira et al, 2015; Teixeira et al, 2016). …”
Section: 0 Discussionsupporting
confidence: 65%
“…Simulations 5 and 6 predict that a downgraded ET opening efficiency will be expressed as a less efficient MEPR for those periods which is accompanied by a consequent negative shift in the EV-MEEPG, effects validated by the change in MEEPG (tympanometric pressure) observed for children and adults during natural and experimental upper respiratory viral infections (Antonio et al, 2002; Buchman et al, 1995; Moody et al, 1998). In addition, emergent features of the model such as physiologic ME species-pressures (Simulation 6), the negative EV-MEEPG for all ET opening efficiencies not equal to 1 (Simulation 3), and the perfusion-limitation on the rate of MEEPG change (Simulations 2, 3) are consistent with clinical measurement (Antonio et al, 2002; Felding et al, 1987; Hergils et al, 1990; Hergils et al, 1997; Moody et al, 1998; Sade et al, 1993) and experimental results (Buchman et al, 1995; Teixeira et al, 2015; Teixeira et al, 2016). …”
Section: 0 Discussionsupporting
confidence: 65%
“…This model shows that downgraded MEPR caused by low, but not 0, ET opening efficiency can be partly restored by an intervention that decreases the transMEM inert gas exchange-rate as for, example, treatment with vasoactive drugs 12 . While provocative, the introduction of any such treatment to improve MEPR with the goal of reducing the morbidity burden attributable to hearing loss and ME pathology in “at risk” populations defined by constitutively low ET opening efficiency is premature and overly ambitious.…”
Section: Discussionmentioning
confidence: 85%
“…One recently published human experiment showed that pharmacologically induced mucosal vasoconstriction decreased the ME gas demand and, specifically, that oral administration of a single standard dose of pseudoephedrine HCL, a drug with well characterized vasoconstrictive effects, decreased the basal transMEM N 2 O exchange-rate by approximately 33% 12 . That effect was attributed to a decreased ME mucosal blood perfusion rate consequent to the decreased ME mucosal blood volume under conditions of drug-induced vasoconstriction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This was a randomized, double-blind, placebo-controlled, cross-over study requiring that participants complete paired N 2 O breathing sessions at a minimum 1-week interval 12,13 . Prior to subject entry, a pharmacist prepared the two challenge materials according to a randomization code and supplied them to the investigators as identical intranasal atomization devices (LMA MAD Nasal, Wolfe-Tory Medical Inc, Salt Lake City, UT) labeled only with session and subject numbers.…”
Section: Methodsmentioning
confidence: 99%